The Impact of Deposit Money Bank's Agricultural Credit on Agricultural Productivity in Nigeria: Evidence from an Error Correction Model - Ogbuabor, Jonathan E.; Nwosu, Cynthia A. (International Journal of Economics and Financial Issues, 2017)
This paper examined the impact of deposit money bank agricultural credit on agricultural productivity in Nigeria using an error correction model and annual time series data for the period 1981 to 2014. The results indicate that an equilibrium relationship exists between the variables. In addition, we find that deposit money bank's agricultural credit impacts positively and significantly on agricultural productivity in the long-run, but this impact is quite negligible in the short-run. We also find that agricultural land and labour force impact negatively on agricultural productivity both in the long-run and short-run. However, the impact of climate change variables, namely annual rainfall and average temperature remained negligible throughout. The paper therefore supports policies that will enhance and sustain the availability of bank credits at affordable interest rates for the agricultural sector, ensure easy access to land for agricultural purposes, and mechanize the agricultural system to attract the youth population. Keywords: Deposit Money Bank; Agricultural Credit; Agricultural Productivity; Error Correction Model; Nigeria. JEL Classifications: E51; Q14; O13; C22; N57